Transcriptional coactivator Cited2 induces Bmi1 and Mel18 and controls fibroblast proliferation via Ink4a/ARF. - Kranc, K; Bamforth, S; Bragança, J; Norbury, C; van Lohuizen, M; Bhattacharya, S (2003)
Cited2 (CBP/p300 interacting transactivator with ED-rich tail 2) is required for embryonic development, coactivation of transcription factor AP-2, and inhibition of hypoxia-inducible factor 1 transactivation. Cited2 is induced by multiple growth factors and cytokines and oncogenically transforms cells. Here, we show that the proliferation of Cited2(-/-) mouse embryonic fibroblasts ceases prematurely. This is associated with a reduction in growth fraction, senescent cellular morphology, and increased expression of the cell proliferation inhibitors p16(INK4a), p19(ARF), and p15(INK4b). Deletion of INK4a/ARF (encoding p16(INK4a) and p19(ARF)) completely rescued the defective proliferation of Cited2(-/-) fibroblasts. However, the deletion of INK4a/ARF did not rescue the embryonic malformations observed in Cited2(-/-) mice, indicating that INK4a/ARF-independent pathways are likely to be involved here. We found that Cited2(-/-) fibroblasts had reduced expression of the polycomb-group genes Bmi1 and Mel18, which function as INK4a/ARF and Hox repressors. Complementation with CITED2-expressing retrovirus enhanced proliferation, induced Bmi1/Mel18 expression, and decreased INK4a/ARF expression. Bmi1- and Mel18-expressing retroviruses enhanced the proliferation of Cited2(-/-) fibroblasts, indicating that they function downstream of Cited2. Our results provide genetic evidence that Cited2 controls the expression of INK4a/ARF and fibroblast proliferation, at least in part via the polycomb-group genes Bmi1 and Mel18.